Testing Mitigation in Safety Critical Systems: Trade-Off Analysis of Various Testing Criteria - Salwa M. Elakeili , Salwa M. Elakeili (Scientific Journal of University of Benghazi, 2020)
This is the first paper of a set of papers dealing with cost of failures. In Safety Critical Systems (SCSs), trade -off the cost of failures (due to lack of testing) against the cost of testing is essential. Usually stronger test criteria are more costly to test, but also more effective at finding faults which if not exposed during testing could lead to operational failures incurring their cost. This paper presents a trade-off cost model that evaluates various criteria for testing mitigation of failures against the cost of defective mitigation. Failure Mode Effect and Criticality Analysis (FMECA) are used to quantify cost of failure, measure the return on investment (ROI) for mitigation test criteria.